Evaluation of the Permeability of Clay-Lime Mixtures for Hazardous Waste Insulation Barriers, Case of Southern Algeria (Adrar) - Khedidja, Belaidi; Abdeldjalil, Zadjaoui; Belkacem, Mekerta; Abdelkader, Bassoud; Mohamed-Amine, Allal (Trends in Sciences, 2024)
Containment of hazardous waste is one of the methods that can be used today for its disposal worldwide, especially in landfills. In order to preserve groundwater, landfills are constructed on a natural or reconstituted clay layer of low permeability, known as a passive safety barrier. This paper presents an experimental laboratory study that aims to upgrade local materials for use as a passive barrier in the bottoms of hazardous waste storage facilities (HWSCs). The basic materials are clays from the Adrar region in southern Algeria. An experimental study based on physical-chemical characterization and mechanical tests was performed on 2 samples of clayey soils (AA, Adrar clay, and AB, Bouda clay). Physico-chemical and mechanical characterization of Adrar clay (AA) mixtures with lime was conducted to minimize swelling and improve the studied soil. The permeability criterion allowed the adoption of an optimal mixture of Adrar clay + 6 % lime for a permeability lower than 10–12 m/s. HIGHLIGHTS Ideal solution to protect natural groundwater resources using local materials, clay and lime Large area exceeding 30 km2 of clay sources and including sources of oil pollution Noticeable improvement in clay properties thanks to the addition of lime to reduce swelling The treated clay has a very low permeability value, lower than 10−12 m/s and is ideal for hazardous waste storage centers GRAPHICAL ABSTRACT